Wood-based solutions for forests and people: An editorial to this Special Issue - Kim, Y.-S.; Baral, H.; Rhee, H.; Pagdee, A.; Gautam, A.; Saxena, A. (Elsevier, 2022)
Tress in or outside forests have been essential in human health and well-being since the beginning of time as ecosystem goods, such as food, timber, energy, water, and other services such as climate regulation and watershed conservation. Wood is an indefinitely renewable natural resource when managed sustainably. Wood-based solutions, such as growing and utilizing woody biomass for energy, building and infrastructure construction, and as raw materials for a variety of wood products, provide a unique opportunity to tackle global sustainability challenges, such as rural development, poverty alleviation and climate change, as well as increasing food and energy security and reducing vulnerability to natural disturbances, such as storm protection and flood regulation. This special issue aims to advance our understanding of rural economic development opportunities through wood-based solutions, including climate smart agroforestry and timber harvests, especially from small-scale tree plantations owned or controlled by small holders and community groups, or from forest thinning treatments and salvage logging to improve forest health in public lands.